Clozapine effects on adenylyl cyclase activity and serotonin type 1A receptors in human brain post-mortem. (April 2014) - Marazziti, Donatella; Baroni, Stefano; Palego, Lionella; Betti, Laura; Giannaccini, Gino; Castagna, Maura; Naccarato, Antonio G; Luccachini, Antonio; Catena-Dell'Osso, Mario; Dell'Osso, Liliana
Although the pharmacological profile of the atypical antipsychotic clozapine has been extensively studied in animal models, little information is available on its effects in the human brain. In particular, much interest is focused on the understanding of clozapine activity on serotonin (5-HT) neurotransmission, particularly on 5-HT receptor of type 1A (5-HT1A ) that seems to play a pivotal role in the control of the 5-HT system. The present work, therefore, aimed at evaluating the effects of clozapine and its major metabolite, norclozapine, on the modulation of adenylyl cyclase (AC) velocity via 5-HT1A receptors in human post-mortem brain regions, in particular the prefrontal cortex, hippocampus and raphe nuclei. Concomitantly, the ability of the two compounds to displace the specific binding of the 5-HT1A receptor agonist [3H]-8-hydroxy-(2-di-N-propylamino) tetralin ([ 3 H]-8-OH-DPAT) was evaluated in the same brain areas. The results showed that both clozapine and norclozapine, although with a 20-fold lower affinity, displaced [ 3 H]8-OH-DPAT binding in all of the brain regions analysed, suggesting their interaction with 5-HT1A receptors. At the same time, clozapine and, to a lesser extent, norclozapine were found to inhibit the forskolin (FK)-stimulated AC system, while decreasing cyclic adenosine monophosphate (cAMP) concentrations in the hippocampus only. The receptor characterisation of the clozapine effect on AC observed in the hippocampus by the use of antagonists showed a mixed profile, involving not only the 5-HT1A receptor but also a muscarinic (M) receptor subtype, most likely the M4 one. These findings, while considering all the limitations due to the use of post-mortem tissues, are strongly suggestive of a region-dependent pharmacological action of clozapine in the human brain that may explain its peculiar clinical effects and open up research towards novel targets for future antipsychotic drugs.